Review on polymer electrolyte in dye-sensitized solar cells (DSSCs). (May 2015) - Su'ait, M.S.; Rahman, M.Y.A.; Ahmad, A.
Highlights: Review on the utilization of polymer electrolyte (PE) in DSSCs is presented. Varieties of PE composition with the maximum η up to 8.0% are discussed. We predicted that in coming years, polyILs will dominant in DSSCs. Abstract: The dependence of dye-sensitized solar cells (DSSCs) on the liquid electrolytes set the limitation and restriction on the expending of the DSSC module fabrication. Moreover, the reductions in its performances were observed as consequences from electron recombination in semiconductor–liquid electrolytes interfaces. This comes back to the question of the behavior of this type of cells, toward the volatilization of redox-electrolytes solution at the semiconductor/electrolyte interface. A more complicated situation arises when the photoanode is in contact with the volatilization of redox-electrolytes solution that affects the charge distribution at the semiconductor–electrolyte interface, and initiated photocorrosion on photoelectrode. The finding of ionic conductivity in polymer material complexed with salt gives a breakthrough to the development of DSSC devices. This article reviews the various approached taken by different perspectives in increasing the solid-state and quasi-solid DSSCs performances utilized solid and gel polymeric electrolytes. From there, a collectives data of power conversion efficiencies and roles played by solid and gel polymeric electrolytes in DSSC were tabularized. Throughout the review process, we predicted that in coming years, polyionic liquids (polyILs) will dominant the polymer electrolyte application in DSSCs due to its unique characteristics.